1983
DOI: 10.1177/014107688307600506
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Isolated Mammary Carcinoma Cells in Marrow of Patients with Primary Breast Cancer

Abstract: Single cells from mammary carcinoma infiltrating bone marrow can be detected in marrow aspirates using immunocytochemical stains for epithelial membrane antigen (EMA). This technique has been used to examine marrow aspirates taken from multiple sites from 24 patients at surgery for breast cancer. Ten of these patients had EMA-positive cells in their marrow, while 32 marrow samples from patients who did not have carcinoma were negative. These results have been combined with those obtained by taking aspirates fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Our results are consistent with those of a number of other published reports. Schoenfeld et al" detected the MUC1 transcript in lymph nodes from patients without cancer by using a simple RT-PCR assay with primers that were distinct from ours and from those of Noguchi et al 910 Immunocytochemical studies in which MUC1 antibodies were used to detect carcinomatous micrometastases in bone marrow demonstrated weak cytoplasmic staining in hematopoietic cells, 35 attributed to nonspecific binding of antibody. Our data suggest this so-called nonspecific staining reaction may, in fact, reflect a low level of MUC1 expression in hematopoietic cells.…”
Section: Discussionmentioning
confidence: 61%
“…Our results are consistent with those of a number of other published reports. Schoenfeld et al" detected the MUC1 transcript in lymph nodes from patients without cancer by using a simple RT-PCR assay with primers that were distinct from ours and from those of Noguchi et al 910 Immunocytochemical studies in which MUC1 antibodies were used to detect carcinomatous micrometastases in bone marrow demonstrated weak cytoplasmic staining in hematopoietic cells, 35 attributed to nonspecific binding of antibody. Our data suggest this so-called nonspecific staining reaction may, in fact, reflect a low level of MUC1 expression in hematopoietic cells.…”
Section: Discussionmentioning
confidence: 61%
“…Our most recent studies have shown that EMA positive cells can be found in the marrows of approximately one third of patients at the time of surgery for a primary breast cancer (Dearnaley et al, 1983).…”
mentioning
confidence: 99%
“…Anti-EMA antiserum was also shown to be useful for differentiating anaplastic carcinoma from malignant lymphomas and for the recognition of spindle cell epithelial malignancies . More recently it has been reported that the antiserum may be used to detect neoplastic cells in serous effusions and also in bone marrow smears in which they cannot be identified by routine haematological examination (Dearnaley et al, 1983;Redding et al, 1983).…”
mentioning
confidence: 99%